Evaluation of Cytotoxic Potential of Classical Siddha Medicine Padikara Parpam in Human Monocytic Leukemic Cell Lines (THP-1) - Karanath-Anilkumar, Aswathy; Munuswamy-Ramanujam, Ganesh; Soman, Vinayak; Sampangiramulu, Shree Devi Munusamy; Parameswaran, Sathiyarajeswaran (Indian Journal of Pharmaceutical Education and Research, 2023)
Introduction: Padikara Parpam (PP), is one among the highly regarded Siddha medicine that is been traditionally claimed for its anti-proliferating and anti-carcinogenic properties. Objectives: In the present work, we investigated the cytotoxic effects of PP in a cellular model of Human leukemia (Human monocytic cell lines (THP-1). Materials and Methods: Determination of cell viability was assessed by the 3-[4, 5-dimethylthiazol-2-yl]-2, 5-diphenyl-tetrazolium bromide (MTT) assay and by using Confocal Laser Scanning Microscope (CLSM). Fluorescence-activated single cell sorting (FACS), and 2'-7'-Dichloro-Dihydro-Fluorescein Diacetate (DCFH-DA) mediated intracellular Reactive Oxygen Species (ROS) measurements were also carried out to understand the effect of PP on THP-1 cells. Results: PP induced cytotoxic effects against THP-1 in a concentration-dependent manner (6.02% - 92.7%), with the highest cytotoxicity at 0.5 mg/mL concentration of PP. The IC50 values of PP in THP-1 cell lines were 0.115 mg/mL. The result from the MTT assay was further confirmed by CLSM reports. The images of Acridine orange/Ethidium bromide stained THP-1 cells treated with PP (IC50 concentration) indicated red fluorescence compared to the control cells which showed only green fluorescence. The images indicated the induction of apoptosis by the study drug. FACS and DCFH-DA based intracellular ROS measurements indicated the ability of PP to increase intracellular ROS levels in a concentration dependent manner. Thereby indicating at a possible ROS mediated apoptotic mechanism of action. Conclusion: These results suggest that with further clinical studies, PP could be used as an economic and effective anti-leukemic drug in patients suffering from leukemia.
Keywords: Siddha medicine; Padikara Parpam; Human Monocytic cell lines; Cytotoxic effects; Confocal Laser Scanning Microscope; MTT assay; Intracellular ROS assay